2005
DOI: 10.1111/j.0908-8857.2005.03323.x
|View full text |Cite
|
Sign up to set email alerts
|

Host use strategies of individual female brown‐headed cowbirdsMolothrus aterin a diverse avian community

Abstract: Strausberger, B. M. and Ashley, M. V. 2005. Host use strategies of individual female brown-headed cowbirds Molothrus ater in a diverse avian community. Á/ J. Avian Biol. 36: 313 Á/321.Although it is well established that brown-headed cowbirds Molothrus ater are host generalists, the parasitism strategies of individual females are not well documented.Here we use microsatellite genotyping to characterize host use by individual female cowbirds. Of 205 offspring sampled at a site in northeastern Illinois during on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Individual female cowbirds sometimes specialize on a particular host species and in other cases use multiple hosts (Alderson et al, 1999;Strausberger and Ashley, 2005), and host usage by individual female cowbirds is an area in need of further research. Estimates of the numbers of eggs laid by individual females in the wild range from 13 to more than 40 (Scott and Ankney, 1983;Fleischer et al, 1987;Alderson et al, 1999; see also Holford and Roby, 1993), but there is some consensus that cowbirds lay eggs on about 70-80% of the days during their breeding season (Fleischer et al, 1987).…”
mentioning
confidence: 99%
“…Individual female cowbirds sometimes specialize on a particular host species and in other cases use multiple hosts (Alderson et al, 1999;Strausberger and Ashley, 2005), and host usage by individual female cowbirds is an area in need of further research. Estimates of the numbers of eggs laid by individual females in the wild range from 13 to more than 40 (Scott and Ankney, 1983;Fleischer et al, 1987;Alderson et al, 1999; see also Holford and Roby, 1993), but there is some consensus that cowbirds lay eggs on about 70-80% of the days during their breeding season (Fleischer et al, 1987).…”
mentioning
confidence: 99%
“…Cowbird chicks were located predominantly in nests of the Eastern Phoebe (Sayornis phoebe, hereafter: Phoebe) (89% of n = 57 samples from 45 nests), with additional single Cowbird chick samples obtained from parasitized nests of Song Sparrows (Melospiza melodia) (n = 3), Dark-eyed Juncos (Junco hyemalis) (n = 1), and House Finches (Carpodacus mexicanus) (n = 2, cross-fostered as eggs into non-parasitized Phoebe nests so that the chicks survived to fledging; Kilner et al 2004). Multiple parasitism events in this data set were only detected in Phoebe nests; thus, to avoid the confound of covariation between host species use and parasite genetic structure (Strausberger and Ashley 2005) within our samples, we also repeated our genetic analyses with cowbird chicks sampled from Phoebe nests only (see below). Previous research at this site on Eastern Phoebes indicated significant spatial structure of cowbird parasitism within and across years (Hauber 2001;Hauber et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This is perhaps because community-wide parasitism patterns mask host choice decisions and strategies of individual cowbirds. Current studies of host selection by individual cowbirds suggest that although most females are host generalists (i.e., parasitize [1 host species), they also exhibit selectivity that appears adaptive (Woolfenden et al 2003;Strausberger and Ashley 2005;Ellison et al 2006). Differences in host defenses, including aggression, nest attentiveness, or nest concealment, may also affect the ability of a cowbird to parasitize a particular host species.…”
Section: Patterns Of Parasitism Levels Among Hostsmentioning
confidence: 99%